Growth suppression of non-small lung carcinoma cell H1299 transfected with p53 and p73B - Hayati, Rahma Fitri; Deny Susanti, Darnis; Arief Ichwan, Solachuddin Jauhari (2010)
p53 gene has been hailed to have important roles in maintaining genomic integrity. The critical roles of this tumor suppressor in cell cycle, DNA repair, and opoptosis profoundly contribute to development of cancer. p53 mutations have been found in almost fifty percent of all cancer types, including lung cancers. Hence, the idea of restoring the normal function of p53 gene by exogeous p53 replacement therapy has been discussed and investigated in order to overcome cancer. However, introduction of wild-type p53 protein is unable ot induce apoptosis in all tumor cases, at least in part, due to their resistance to exogenous p53. p73Bhas been regarded as one of the strongest candidate as it is similar to p53 in many aspects: structural homology, transactivation of p53-downstrean genes, and induction of apoptosis. It has been reported that a similar therapeutic strategy can be successfully applied in p73 activation as well. Interestingly, the mutation of this gene has been rarely found in cancer, suggesting different mechanism or regulation pathway of this gene. The aim of this study is to compare the tumor suppressor activity of p53 and p73B, on p53 and p73B constructed in pCMV plasmid was conducted through chemical mediated transfection. Introduction of exogenous expression of p53 significantly suppress colony formation of H1299 cells under G418 selection while p73B could partially suppress the colony formation. Consistently, exogenous p53 and p73B raise expression of p21/Waf gene. These results show overlapping regulation performed by p73B which suggest its application as alternative candidate in gene therapy.